2020
DOI: 10.3390/molecules25235698
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization Profile of Human Transthyretin Variants with Distinct Amyloidogenicity

Abstract: One of the molecular hallmarks of amyloidoses is ordered protein aggregation involving the initial formation of soluble protein oligomers that eventually grow into insoluble fibrils. The identification and characterization of molecular species critical for amyloid fibril formation and disease development have been the focus of intense analysis in the literature. Here, using photo-induced cross-linking of unmodified proteins (PICUP), we studied the early stages of oligomerization of human transthyretin (TTR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
0
14
0
1
Order By: Relevance
“…In Figures 3A and 4A, small aggregates of several hundred nm in size were observed by CDE treatment. Because TTR has been reported to form up to octameric structures, 50 nm or less, as soluble oligomers, 27 the aggregates observed by CDE treatment are considered to be TTR amyloid fibrils (different from oligomers). According to the Th-T assay, both CDE and CDE/shRNA significantly reduced the amount of TTR V30M amyloid fibrils, but while CDE/shRNA disrupted approximately 55% of fibrils, CDE alone only disrupted approximately 36% (Figure 4B).…”
Section: Characterization and Optimization Of Cde/shrnamentioning
confidence: 99%
“…In Figures 3A and 4A, small aggregates of several hundred nm in size were observed by CDE treatment. Because TTR has been reported to form up to octameric structures, 50 nm or less, as soluble oligomers, 27 the aggregates observed by CDE treatment are considered to be TTR amyloid fibrils (different from oligomers). According to the Th-T assay, both CDE and CDE/shRNA significantly reduced the amount of TTR V30M amyloid fibrils, but while CDE/shRNA disrupted approximately 55% of fibrils, CDE alone only disrupted approximately 36% (Figure 4B).…”
Section: Characterization and Optimization Of Cde/shrnamentioning
confidence: 99%
“…Dasari et al showed that wild-type TTR tends to form linear oligomers, while the G53A TTR variant forms annular oligomers with pore-like structures [ 48 ]. Frangolho et al compared the oligomerization processes of wild-type TTR and several TTR variants (V30M, L55P and T119M) and found distinct oligomerization kinetics but a similar oligomerization mechanism [ 49 ]. The oligomerization kinetics of the wild-type TTR and TTR variants showed a good correlation with their amyloidogenic potential, and the most amyloidogenic variants aggregated faster (L55P > V30M > wild-type).…”
Section: Molecular Mechanisms Of Amyloidosismentioning
confidence: 99%
“…This observation indicated that the protofibril might be formed by the mechanism of adding 15-nm oligomers to the end of the protofibril [ 73 ]. More recently, Frangolho et al used photo-induced crosslinking experiments to capture up to octameric species during acid-induced TTR aggregation at pH 3.6 [ 74 ]. They found that amyloidogenic variants of TTR showed faster oligomerization rates, and also provided evidence supporting sequential monomeric addition to oligomers.…”
Section: Deformation Of the Ttr Quaternary Structurementioning
confidence: 99%